2021
DOI: 10.1108/mhrj-07-2019-0025
|View full text |Cite
|
Sign up to set email alerts
|

“It’s changed my life!” Evaluation and improvement of a pilot Tier 2 weight management course, “Balance”

Abstract: Purpose This paper aims to describe a service evaluation study of “Balance” – a National Health Service Tier 2 pilot weight management course delivered in a primary care mental health service. The 12 weekly sessions included dietetic, psychological and behavioural elements underpinned by cognitive behavioural theory and “third-wave” approaches, including acceptance and commitment therapy, compassion-focused therapy and mindfulness. Design/methodology/approach A mixed-methods design was used in this service e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…The theme of the “role of program staff” focuses on HCPs directly involved in the lifestyle intervention program, of which 15 studies reported on. Eight studies described barriers, 26,32,33,35,37,39,43,50 and 11 described facilitators 27,35,38,39,42,43,45,47,49–51 . The two most commonly reported barriers were a lack of active follow‐up and program staff being difficult to reach for participants.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The theme of the “role of program staff” focuses on HCPs directly involved in the lifestyle intervention program, of which 15 studies reported on. Eight studies described barriers, 26,32,33,35,37,39,43,50 and 11 described facilitators 27,35,38,39,42,43,45,47,49–51 . The two most commonly reported barriers were a lack of active follow‐up and program staff being difficult to reach for participants.…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐six studies reported on the program structure of the lifestyle intervention, of which 19 reported on barriers, 27–29,31–35,37–41,43,45,46,48–50 including disliking certain aspects of the group sessions, feeling that the individual is not the target population, a lack of personalized approach, the program being too much effort, program tools are difficult to use, and the program having too much time between follow‐ups; 25 studies reported on facilitators 25–29,31–36,38–43,45–52 . The most commonly reported facilitators were a program with a personalized approach, liking certain aspects of group sessions, liking certain aspects of the program, monitoring of health and weight status, and programming tools that were seen as helpful and flexibility in scheduling the sessions.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations